SAPHO syndrome as a therapeutic challenge: case report - Gerkowicz, Agnieszka; Michalak-Stoma, Anna; Juszkiewicz-Borowiec, Maria; Wielosz, Ewa; Chodorowska, Grażyna (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction. SAPHO is a rare syndrome characterized by synovitis, acne, pustulosis, hyperostosis and osteitis. The aetiology of this syndrome is not fully recognized. Objective. To present a case of a 17-year-old boy with SAPHO syndrome. Case report . A 17-year-old boy was admitted to the Dermatology Department due to severe acne lesions, plantar pustulosis and psoriatic plaques. Skin lesions were accompanied by severe pain of the left knee. The patient reported pain in the anterior chest wall appearing occasionally. On physical examination, limitation of mobility of the thoracic and lumbar vertebral column was noticed. The skin biopsy confirmed the diagnosis of plantar pustular psoriasis. A vertebral column X-ray, chest X-ray, bone scintigraphy and several laboratory tests were performed. Based on clinical, laboratory and radiological findings the SAPHO syndrome was diagnosed. The patient was treated with antibiotics, sulfasalazine, etanercept and methotrexate. Conclusions . The SAPHO syndrome combines bone and join manifestations associated with skin lesions. Due to the unknown aetiology of this syndrome the treatment remains empirical, and therapy should be adapted to the individual patient.